2018
DOI: 10.2196/10777
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Electronic Data Collection System to Support a Large-Scale HIV Behavioral Intervention Trial: Protocol for an Electronic Data Collection System

Abstract: BackgroundAdvancing technology has increased functionality and permitted more complex study designs for behavioral interventions. Investigators need to keep pace with these technological advances for electronic data capture (EDC) systems to be appropriately executed and utilized at full capacity in research settings. Mobile technology allows EDC systems to collect near real-time data from study participants, deliver intervention directly to participants’ mobile devices, monitor staff activity, and facilitate n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Secure data platforms are advised for data collection [1,10,11,19,24]. Investigators in several studies were careful to remove as much identifying participant information as possible, using telephone numbers or participant IDs in the datasets [11,25], recommending that participants immediately delete messages after answering them, and encouraging participants to password protect their phones [16,17,24].…”
Section: The Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Secure data platforms are advised for data collection [1,10,11,19,24]. Investigators in several studies were careful to remove as much identifying participant information as possible, using telephone numbers or participant IDs in the datasets [11,25], recommending that participants immediately delete messages after answering them, and encouraging participants to password protect their phones [16,17,24].…”
Section: The Datamentioning
confidence: 99%
“…Researchers should have a preset plan in place for how to capture supplemental data. A study in Los Angeles utilizing a large electronic data collection system for HIV self-management and prevention/engagement of HIV-negative youth quickly realized that staff needed open-ended running notes to log ad-hoc interactions with participants [24].…”
Section: The Datamentioning
confidence: 99%
“…We anticipate a higher proportion of women in our sample from New Orleans and that while most youth from New Orleans will be African American, youth in Los Angeles will also be Latino and White and predominately GBTY. Further details on each of the ATN CARES studies may be found in the corresponding study protocol papers [112,[115][116][117][118]. Recruitment Process.…”
Section: Peer Support Via Social Mediamentioning
confidence: 99%
“…We hypothesize that by providing rapid STI testing among high-risk adolescent populations, we will find a high prevalence of STIs. We also expect that by providing same-day testing results, we will be able to [20][21][22][23][24].…”
Section: Objectivesmentioning
confidence: 99%